Cardiac ICU´s nursing discharge plan for a patient with Implantable Cardioverter Defibrillator: literature review for an evidenced based nursing practice - Lilian de Souza Alencar; Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
It is about a bibliographical research carried through the period of May until December of 2007. That it has as objective to stand out the Nurse's job in the discharged one of the patient in the one after implant of Implantable Cardioverter defibrillator (ICD) in the unit of high complexity. The period chosen for the bibliographical survey understood last the 5 years. They were built four categories: The impact in the quality of life of the patient and that its familiar after implant of ICD; The importance the orientation of family; Plan of orientation of nursing in the discharged: immediate and mediate cares to the implantation of ICD, Plan of orientation of nursing in the discharged: possible limitations and a new life style. Identified the necessity of a team to multidiscipline in the discharged of this patient, importance of the nurse's job in this process was recognized it.